Business and Human Rights Concerns in the Indonesian Textile Industry - Iman Prihandono; Fajri Hayu Religi (Universitas Airlangga, 2019)
Indonesia is the tenth largest textile exporter in the world. The textile industry has long been the major industry to absorb labour force in the country. The textile industry substantially contributes to the national economic growth by employing 3.58 million workers, or 21.2 per cent of the total labour force in the manufacturing industry. The textile business has been growing over the previous decade. Based on the Bank of Indonesia report, this industry significantly contributes to the Gross Domestic Product (GDP) of Indonesia. The contribution increased from Rp96.3trillion (US7billion) in 2010 to Rp139.4trillion (US10.2billion) in 2015. However, the textile industry in Indonesia does not only positively contribute to the country’s economic growth, it also creates negative impacts, such as environmental issues. As will be explained further, these environmental impacts include environmental damage caused to the Citarum River and Sukoharjo. The textile industry’s contribution to pollution is also high at a global level. Among the G20 countries, Indonesia is ranked 2nd for the highest levels of water pollution caused by the textile industry with 29.25 per cent, slightly below Turkey (32.21 per cent). Even though most of the international brands, such as GAP, H&M and Inditex, have already adopted human rights standards and policies, there are still many cases that show the failure of these companies to uphold human rights. For this reason, the implementation of international standards is needed to achieve a more sustainable textile industry. This article discusses business and human rights concerns in relation to the Indonesian textile industry. It addresses several environmental issues caused by the textile industry, discusses human rights standards and policies in the textile industry, and finally shows possible ways of implementing such international standards (i.e. Eco Label and the Bangladesh Accord) in Indonesia.